2008
DOI: 10.1089/pho.2007.2134
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Processes in Cells after Light Absorption Do Not Depend on the Degree of Polarization: Implications for the Mechanisms of Laser Phototherapy

Abstract: The biological effect (stimulation of cell attachment) of light with lambda = 637 nm on cells in our model system was pronounced, but did not depend on the degree of light polarization. Elementary processes in cells (light absorption and photochemistry) do not appear to depend on the degree of light polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…14,15 As discussed below, it is a remarkable finding that in mammalian tissues, the photosensitivity of certain chromophores conserves physiologic significance, in spite of their adaptation to naturally function without external photons. 16 A distinctive property of chromophores is that they absorb particular wavelengths and reflect others, thus conferring specific colors to molecules. For example the porphyrin ring in chlorophyll a has peaks of absorption at 430 nm and 662 nm.…”
Section: Hormetic Effects Of Llltmentioning
confidence: 99%
“…14,15 As discussed below, it is a remarkable finding that in mammalian tissues, the photosensitivity of certain chromophores conserves physiologic significance, in spite of their adaptation to naturally function without external photons. 16 A distinctive property of chromophores is that they absorb particular wavelengths and reflect others, thus conferring specific colors to molecules. For example the porphyrin ring in chlorophyll a has peaks of absorption at 430 nm and 662 nm.…”
Section: Hormetic Effects Of Llltmentioning
confidence: 99%
“…Laser biostimulation can obtain different intracellular biological reactions to stimulate regenerative abilities, without undesired adverse effects, reducing also the pharmacological support and its possible invasiveness. Besides explaining many controversies in the field of low-power laser effects (i.e., the diversity of effects, the variable magnitude or absence of effects in certain studies), the proposed redox-regulation mechanism may be a fundamental explanation for some clinical effects of irradiation, for example the positive results achieved in treating wounds, chronic inflammation, and ischemia, all characterized by acidosis and hypoxia [7].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Karu et al showed in an in vitro study that the basic processes of LLLT occurring in HeLa cells were light absorption and photochemistry but that the incident characteristics of photons, such as degree of light polarization, did not affect the biological reactions in LLLT. 23 However, scattering of photons in vivo depends on the microstructure of tissue, and light propagation into biological tissue would therefore change the healing property. For instance, Ribeiro et al investigated the repair of skin burns in rats with a linearly polarized He-Ne laser beam, which was parallel or perpendicular to the direction of the spinal column, at the same laser dose.…”
Section: Introductionmentioning
confidence: 99%